HOW TO OBTAIN ECONOMICALLY EFFICIENT ASPHALT CONCRETE MIXTURES FOR CONSTRUCTIVE AUTOMOBILE ROAD AND STREET PAVEMENTS - V. A. Verenko; V. V. Zankovich (Наука и техника)
The paper describes a methodology for evaluation of technical and economic efficiency of asphalt concrete mixture components. The method allows to perform a directed search for new materials which are used for mixture preparation and it also provides an efficient use of monetary funds. Firstly, it is possible to obtain this result due to optimum price-quality ratio of asphalt mixture which is determined by its service life in a pavement; secondly, it is possible to obtain this result due to  exclusion of errors while selecting components of the asphalt mixture out of the whole range applied presently in the world practice.